PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 003 SUNGAI MANASIB KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Sadikin, Hasby Sadikin; Daud, Damanhuri Daud; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to improve science learning outcomes fourth grade students of SDN 003Sungai Manasib the Academic Year 2013/2014. This study is a quantitative research with design is a class act. Research subjects that fourth grade students of SDN 003 Sungai Manasib as many as 30 students consisting of 20 male students and 10 female students. Research instrument used was a learning device and instrument collection data. The technique of data collection form observation sheet, , quizzes every meeting and daily test of students .. Value of student learning outcomes before PTK 64.5 and increasedto 73.86 in the first cycle and increased again in the second cycle becomes 79.2. Classical completeness before PTK is 30 students in the first cycle increased to 80 and again increased in the second cycle becomes 86.66. So that student learning outcomes can be declared complete klasikal. Of student learning outcomes after PTK can be concluded that the Numbered Heads Together learning model to improve science learning outcomes fourth grade students of SDN 003 Sungai Manasib. Keyword: Cooperative Learning Model types Numbered Heads Together (NHT), Science Learning Outcomes